Impact of Information Bias Analysis on News Consumption Patterns of Digital Platforms in Indonesia - Nurhani Maghfira Wali (PT Agung Media Publisher, 2025)
Digital platforms have become the main source of news for Indonesians, with internet penetration reaching over 77% by 2024. However, the shift to digital news consumption has brought challenges, particularly the presence of analytical information bias such as emotional language, one-sided framing, and the blending of facts with opinions. This study explores how such bias impacts public news consumption behavior in Indonesia. Using a qualitative approach, this research collected data through in-depth interviews with active digital news consumers. Participants were selected purposively to represent different age groups, professions, and digital literacy levels. Data were analyzed thematically to understand patterns in how people perceive and respond to biased news. The study found that many users consume news quickly and uncritically, often influenced by headlines or emotional tone. Analytical bias in news affects how people interpret information, leading to polarized opinions, mistrust in media, and low information literacy. Only a small group of users with higher digital literacy showed efforts to verify and balance the information they receive. Information bias on digital platforms has a complex impact on how Indonesians consume news. It shapes public opinion, weakens critical thinking, and contributes to societal divisions. To address this, collaboration is needed between media, educators, and policymakers to strengthen media literacy and create a healthier information ecosystem. This study is limited by its qualitative scope and sample size; future research could involve broader data collection and mixed methods to deepen the findings.